Real options : evaluating corporate investment opportunities in a dynamic world - Howell, Syd. (London ; New York : Financial Times Prentice Hall, 2001)
Will provide the reader with a comprehensive understanding of the concepts behind real option analysis and how to use them. It demystifies the scientific aura surrounding the subject, giving the reader the understanding necessary to direct or apply real option analysis in any organizational setting.
Includes bibliographical references (p. 295-299) and index.
oif 15/07/14
Loans
Keywords: Investment analysis; Intangible property -- Valuation; Options (Finance) -- Valuation